(3eTGQb GdCfhGQ GdfHhjI aj UMGM GdCNHGQ GdeUWajIs - (3GdMSf Hf eMeO Hf GdMSf Hf MjOQ GdYOhj GdYeQj GdUGZGfj GdMfaj QVqj GdOjf,J (B650 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg eMji GdQee heLQi Gdbde CeG HYO aEfi eP JOQLJ eQGbi GdSQa hdeG JhLfi Gddg JYGdi hOhLfi HJGL eUHGM GdOLi ef UMGM MOjK GdeUWai s
(3BNQgG (B:s
(3YGFTI ef Yed YedkG djS Ydjg CeQfG agh QO CHh gQjQI ef ZOG Edi GdeSLO Ch QGM CYO Gddg dg ai GdLfI fRdkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bSe efg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B279s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1688s
Keywords: (3GdMOjK h GdeUWdMs